Anatomia do caule de Lycopersicon Esculentum Mill., submetido a diferentes tratamentos com reguladores vegetais - Martins, Maria Bernadete Gonçalves [UNESP]; Castro, Paulo Roberto de Camargo e (Brazilian Archives of Biology and Technology, 1998)
The effects of plant growth regulators GA3 50 mg. L-1, NAA 100 mg. L-1, CCC 1500 mg.L-1 and SADH 3000 mg.L-1 on stem anatomy of Lycopersicon esculentum Mill cv. Ângela Gigante were studied. Two sets of experiments were carried out in greenhouse during two separte periods. Anatomical studies , revealed that growth promotors induced increased xylem thickness and increased the number of tracheary elements while the growth retardants decreased xylem thickness and induced fiber formation.
Keywords: plant growth regulators; anatomy; stem; Lycopersicon esculentum